THE CORRELATION BETWEEN TEACHERS’ SELF-EFFICACY PERCEPTIONS AND TOLERANCE AND PSYCHOLOGICAL WELL-BEING - Gündüz, Yüksel (International Online Journal of Education and Teaching, 2022)
Teachers’ self-efficacy beliefs, tolerance, and psychological well-being are all examined in this study. In this research, a survey model based on correlation was applied. In the 2021-2022 academic year, there are 11578 teachers working in public schools in lkadm, Canik, Atakum, Bafra, and arşamba districts of Samsun province. As a result, the study’s sample size is 678 instructors drawn from the general community using simple random sampling. The study gathered data using the Teacher Self-Efficacy Scale, the Tolerance Scale, and the Psychological Well-Being Scale. Analyzing data required the use of a variety of statistical procedures, including the t test, ANOVA, Pearson-product moment correlation coefficient, and multiple linear regression. Teachers’ self-efficacy perceptions tend to be in the form of "mainly suitable for me," according to the findings of this study. For the most part, teachers’ tolerance levels are characterized by "disagreement" and "poor." In general, teachers’ psychological well-being is rated at the "agree" level and above the average. A statistically positive association between teachers’ self-efficacy and psychological well-being was observed, but no statistically significant correlation was identified with tolerance. However, teachers’ self-efficacy is one of the most important indicators of their psychological well-being even though it is not a strong predictor of their tolerance.